Oblicza autokracji w czeskich dystopiach literackich na wybranych przykładach - Czaplińska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The paper deals with the phenomenon of dystopia in Czech literature before 1989. The main aim of the article is to present some similiar views on totalitarian power and its influence on the individual in Czech novels and short stories: Datum narození nula by Ludmila Freiová, Poselství pro Agla Mathona by Ondřej Neff, Utopie, nejlepší verze by Ivan Kmínek and Maso by Martin Harníček. The purpose of the paper was also to show how in the authors’ visions of autocratic states, administration is taking control over ordinary people and what kind of tools it uses to manipulate them: terror, self-censorship or various addictions.
Keywords: Czeskie dystopie literackie; autokracja w literaturze; Freiová Ludmila; Neff Ondřej; Kmínek Ivan; Harníček Martin